Bridging the disciplinary gap in conservation agriculture research, in Malawi: A review - Hermans, Thirze D.G.; Whitfield, Stephen; Dougill, Andrew J.; Thierfelder, Christian L. (Springer, 2020)
Conservation Agriculture has emerged as a popular form of climate smart agriculture aimed at enhancing climate change resilience for smallholder farmers across Africa. Despite positive biophysical results, adoption rates remain low. It has been acknowledged that improved understanding of farmer decision-making is needed due to the variation in socio-economic and agro-ecological contexts which drives the research agenda to answer the question ‘what forms of Conservation Agriculture work, where, and why?’. To fully understand this question, we need to approach the study of Conservation Agriculture within complex farming systems by collating and integrating different forms of knowledge. In this paper, we discuss (1) a comparison of disciplinary approaches to evaluating Conservation Agriculture in Malawi, (2) the identification of the knowledge gaps that persist at the intersection of these disciplines and (3) recommendations for alternative and interdisciplinary approaches in addressing these knowledge gaps. With a focus on published studies from Malawi, we show that the Conservation Agriculture literature represents two distinct approaches to addressing the question ‘what forms of Conservation Agriculture work, where, and why?’, namely agro-ecological and socio-economic and that neither of these approaches can address the full scope of this question, in particular its ‘why’ component. To overcome these challenges, there is a need for access to compatible, comprehensive data sets, methodological approaches including farmer participation and ethnography, through on-farm trial research as a middle ground between disciplinary approaches.